Pooperativno ovrednotenje nenapetostnega vaginalnega traku (TVT) 2 do 6 let po posegu - Lužnik, Marijan (Zdravniški vestnik, 2006)
Background The purpose of this article is to show the long-term subjective cure rate of urinary incontinence in patients after the tension free vaginal tape (TVT) procedure and eventual correlation of some factors with this cure rate. Methods From December 1999 to July 2004 we performed one hundred and fifty TVT procedures at our Department of Gynecology and Obstetrics. In April 2006, a 2 to 6 year postoperatively, 149 questionnaires were sent to our patients for self-estimation of the cure rate. The subjective evaluation of results of the operation was based on definition of the improvement of continence in percents, with 23 possibilities ranging from -20% to 100%. With tests of correlation we wish to establish eventual connection between the curerate of urinary incontinence and the age of women at the time of operationand the number o fpostoperative years. Statistical significance of eventual influence of independent variables on cure rate was analyzed using nonparametric tests in Statistical Program Package for Social Sciences (SPSS).Results Of 119 answers, in 40 cases (33.6%) patients confirmed that they are completely healthy; and 87 women (73.1%) confirmed at least 70% cure rate. 100 answers confirmed that 87.6% patients had benefited by TVTprocedure even 2 to 6 years postoperatively. Correlation between the long-term cure rateand the patient's age at time of operation had Pearsoy's correlation coefficient r = -0.335 and was statistically significant (p = 0.01). Statistically significuntly different success was still in the groups with regard to the previous hysterectomy (p = 0.005) and the previous surgical procedure for urinary incontinence (p = 0.001). There was no statistically significant difference between the cure rate and the number of postoperative years (p = 0.236). (Abstract truncated at 2000 characters)
Keywords: ankete; Questionnaires; Surgery; therapy; Treatment Outcome; Urinary Incontinence; Urinska inkontinenca; zdravljenje; Zdravljenje, izid